"Production + procurement" outsourcing with competitive contract manufacturer's partial learning and supplier's price discrimination. (14th November 2020) - Niu, Baozhuang; Zeng, Fanzhuo; Chen, Lei
Abstract: It is widely observed that many original equipment manufacturers (OEMs) have relied on contract manufacturers (CMs) for production, even if the CMs have self‐branded business. However, outsourcing "production + procurement" indicates deep cooperation between OEMs and CMs, and hence, induces the CMs to partially but legally learn the OEM's innovations. In this paper, we formulate an OEM's procurement outsourcing decisions to a competitive CM when the latter has partial learning ability. We formulate the OEM's trade‐offs between its procurement cost saving and the intensified downstream competition because of the competitive CM's improved products. We find that the OEM prefers outsourcing "production + procurement" when the competitive CM's learning ability is either low or high. The CM's high learning ability will lower the OEM's marginal revenue but the OEM can save innovation investment cost if he outsources "production + procurement". We also study the impact of the competitive CM's improved learning ability and the OEM's license fee charged to the competitive CM.